The man in song : a discographic biography of Johnny Cash - Alexander, John M., 1956- (University of Arkansas Press, 2018)
There have been many books written about Johnny Cash, but The Man in Song is the first to examine Cash's incredible life through the lens of the songs he wrote and recorded. Music journalist and historian John Alexander has drawn on decades of studying Cash's music and life, from his difficult depression-era Arkansas childhood through his death in 2003, to tell a life story through songs familiar and obscure. In discovering why Cash wrote a given song or chose to record it, Alexander introduces readers anew to a man whose primary consideration of any song was the difference music makes in people's lives, and not whether the song would become a hit. The hits came, of course. Johnny Cash sold more than fifty million albums in forty years, and he holds the distinction of being the only performer inducted into the Rock and Roll Hall of Fame, the Country Music Hall of Fame, the Songwriters Hall of Fame, and the Gospel Music Hall of Fame. The Man in Song connects treasured songs to an incredible life. It explores the intertwined experience and creativity of childhood trauma. It rifles through the discography of a life: Cash's work with the Tennessee Two at Sam Phillips's Sun Studios, the unique concept albums Cash recorded for Columbia Records, the spiritual songs, the albums recorded live at prisons, songs about the love of his life, June Carter Cash, songs about murder and death and addiction, songs about ramblers, and even silly songs. Appropriate for both serious country and folk music enthusiasts and those just learning about this musical legend, The Man in Song will appeal to a fan base spanning generations. Here is a biography for those who first heard "I Walk the Line" in 1956, a younger generation who discovered Cash through songs like his cover of Trent Reznor's "Hurt," and everyone in between